An Investigation and Implementation of Some Binary Search Tree Algorithms - Walker, Aldon N. (My University, 1974)
This project documents the results of an investigation into binary search trees. Because of their favourable characteristics binary search trees have become popular for information storage and retrieval applications in a one level store. The trees may be of two types, weighted and unweighted. Various algorithms are presented, in a machine independent context, for both types and an empirical evaluation is performed. An important software aid used for graphically displaying a binary tree is also described.
Keywords: Computer Engineering; Computer Engineering